2006
DOI: 10.1007/s11010-006-9218-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with alcoholic extract of shape Crataegus oxycantha (AEC) activates mitochondrial protection during isoproterenol – induced myocardial infarction in rats

Abstract: Crataegus oxycantha (hawthorn) is used in herbal and homeopathic medicine as a cardiotonic. The present study was done to investigate the effect of the alcoholic extract of Crataegus oxycantha (AEC) on mitochondrial function during experimentally induced myocardial infarction in rat. AEC was administered orally to male albino rats (150-200 g), at a dosage of 0.5 ml/100 g body weight/day, for 30 days. At the end of the experimental period, the animals were administered isoproterenol (85 mg/kg body weight, s.c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…As mitochondria produce 95% of energy necessary for heart function, therapeutic agents that could influence mitochondrial dysfunction are of special importance. Alcoholic extract of Crataegus oxyacantha (AEC) pretreatment maintained mitochondrial antioxidant status and prevented mitochondrial lipid peroxidative damage and decrease in Krebs cycle enzymes induced by isoproterenol in rat heart [29]. Another research showed that Crataegus fruit extracts decreased the mitochondrial membrane potential by 1.2–4.4 mV measured with a tetraphenylphosphonium-selective electrode and H 2 O 2 production measured fluorometrically.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…As mitochondria produce 95% of energy necessary for heart function, therapeutic agents that could influence mitochondrial dysfunction are of special importance. Alcoholic extract of Crataegus oxyacantha (AEC) pretreatment maintained mitochondrial antioxidant status and prevented mitochondrial lipid peroxidative damage and decrease in Krebs cycle enzymes induced by isoproterenol in rat heart [29]. Another research showed that Crataegus fruit extracts decreased the mitochondrial membrane potential by 1.2–4.4 mV measured with a tetraphenylphosphonium-selective electrode and H 2 O 2 production measured fluorometrically.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…The action of these compounds on the cardiovascular system has led to the development of leaf and flower extracts, which are widely used in Europe. Other chemical constituents includes vitamin C, saponins, tannins, cardiotonic amines (phenylethylamine, tyramine, isobutylamine, O-methoxy phenylethylamine, choline and acetylcholine), purine derivatives (adenosine, adenine, guanine, caffeic acid, amygdalin), triterpene acids ursolic acid (Verma et al, 2007 Jayalakshmi et al, 2006;Garjani et al, 2000).…”
Section: Chemistrymentioning
confidence: 99%
“…These amines were responsible for in vitro activity of Crataegus extracts on the guinea pig papillary muscle (Wagner & Grevel, 1982) and it also raised intracellular calcium thus prolongs the action potential, which supports for its inotropic activity (Kocyildiz et al, 2006). In another study, alcoholic extract of Crataegus oxycantha (AEC) was found to maintain mitochondrial antioxidant status, decreased Kreb's cycle enzymes induced by isoproterenol in rat heart and prevented mitochondrial lipid peroxidative damage (Jayalakshmi et al, 2006). to ameliorate post-angioplasty restenosis and prevent balloon catheter-induced intimal hyperplasia (Furst et al, 2010).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Superoxide dismutase, which catalysis the dismutation of two superoxide radicals to form hydrogen peroxide and molecular oxygen. Therefore, the H 2 O 2 created is deactivated by either catalase or the GSH redox system containing of reduced glutathione as the cofactor for GP X and glutathione reductase [32]. Citrus aurantium pre-co-treatment exhibited a substantial increase in the level of serum SOD and catalase.…”
Section: Discussionmentioning
confidence: 99%